2018
DOI: 10.3390/nu10010109
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Counting in Children and Adolescents with Type 1 Diabetes

Abstract: Carbohydrate counting (CC) is a meal-planning tool for patients with type 1 diabetes (T1D) treated with a basal bolus insulin regimen by means of multiple daily injections or continuous subcutaneous insulin infusion. It is based on an awareness of foods that contain carbohydrates and their effect on blood glucose. The bolus insulin dose needed is obtained from the total amount of carbohydrates consumed at each meal and the insulin-to-carbohydrate ratio. Evidence suggests that CC may have positive effects on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 66 publications
4
64
0
7
Order By: Relevance
“…Hypoglycemia has been considered as a major barrier to the proper glycemic control in diabetic patients [69]. Our analyses revealed that Tangminling reduced blood glucose mildly, without hypoglycemic events reported.…”
Section: Radix Trichosanthismentioning
confidence: 60%
“…Hypoglycemia has been considered as a major barrier to the proper glycemic control in diabetic patients [69]. Our analyses revealed that Tangminling reduced blood glucose mildly, without hypoglycemic events reported.…”
Section: Radix Trichosanthismentioning
confidence: 60%
“…This gives them the flexibility of eating different meal sizes with adjustment of insulin doses according to the carbohydrate content of their meals. 4 This study found that bolus insulin requirements estimated by the 500 rule were lower than the actual bolus doses used by the study participants. These results confirmed the findings of other studies, which demonstrated that the 500 rule underestimated the insulin requirements for children and adolescents with T1DM.…”
Section: Discussionmentioning
confidence: 71%
“…Estimation of the ICR is essential for calculation of bolus insulin doses in children and adolescents with T1DM using carbohydrate counting. This gives them the flexibility of eating different meal sizes with adjustment of insulin doses according to the carbohydrate content of their meals …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations